2022
DOI: 10.1007/s11606-021-07251-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Worker Mental Health After the Initial Peak of the COVID-19 Pandemic: a US Medical Center Cross-Sectional Survey

Abstract: BACKGROUND: There is a paucity of data on the mental health impact of the Coronavirus disease 2019 (COVID-19) pandemic on United States (US) healthcare workers (HCWs) after the first surge in the spring of 2020. OBJECTIVE: To determine the impact of the pandemic on HCWs, and the relationship between HCW mental health and demographics, occupational factors, and COVID-19 concerns. DESIGN: Cross-sectional survey in an urban medical center (September-November 2020) in Baltimore, MD, in the United States. PARTICIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
58
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 56 publications
9
58
3
2
Order By: Relevance
“…[6][7][8] Fourth, healthcare worker burnout is an important factor that was not assessed and could have affected outcomes. 9 Finally, differing COVID-19 policies and PPE availability during the pandemic's first wave make these results difficult to extrapolate to non-pandemic-related scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Fourth, healthcare worker burnout is an important factor that was not assessed and could have affected outcomes. 9 Finally, differing COVID-19 policies and PPE availability during the pandemic's first wave make these results difficult to extrapolate to non-pandemic-related scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists reported that working overtime, medication supply and patient incivility were factors that affected work. This has been shown in several recent studies in nurses, physicians, and other health care professionals throughout the world 11‐18 . A recent study assessed the psychological response in 467 nurses early in the COVID‐19 pandemic and showed that 54.6% of nurses reported traumatic stress, 54.6% reported depressive symptoms, 32.4% reported insomnia, and 37.3% reported anxiety 17 .…”
Section: Discussionmentioning
confidence: 86%
“…This has been shown in several recent studies in nurses, physicians, and other health care professionals throughout the world. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 A recent study assessed the psychological response in 467 nurses early in the COVID‐19 pandemic and showed that 54.6% of nurses reported traumatic stress, 54.6% reported depressive symptoms, 32.4% reported insomnia, and 37.3% reported anxiety. 17 Another study in 605 health care workers (physicians, nurse practitioners, nurses, physician assistants, patient care technicians, respiratory therapists, social workers, mental health therapists, and case managers) early in the pandemic showed that 14.2% reported depressive symptoms, 43.2% reported mild or high anxiety, 22.3% reported posttraumatic stress disorder (PTSD) symptoms, 46% reported emotional exhaustion, 21.6% reported depersonalization, and 23.1% reported lower resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to physicians and nurses, healthcare workers also include patient care technicians, respiratory therapists, mental health therapists, etc. In the face of clinical uncertainty, in addition to feeling mental stress, they also have a fear of the unknown, perceived social stigma, and workplace safety concerns ( 28 ). Social and family support can effectively alleviate these negative emotions.…”
Section: Discussionmentioning
confidence: 99%